The Impact of Cybervictimization on the Self-Management of Chronic Conditions: Lived Experiences - Zhraa A Alhaboby; Hala Evans; James Barnes; Emma Short (JMIR Publications, 2023)
BackgroundCybervictimization of people with long-term conditions is a disturbing phenomenon with a documented impact on health and well-being. These experiences are primarily examined using quantitative methods, focusing on children and young people. However, research centered on the cybervictimization of adults with chronic conditions is scarce, with limited qualitative input from the victims as experts in their own experiences. ObjectiveThis study aims to understand the impact of cybervictimization on the self-management of long-term conditions among adults with chronic conditions and disabilities in the United Kingdom. MethodsThis paper reports the findings from the qualitative phase of a phenomenologically informed mixed methods study. The biographical disruption concept was used to conceptualize the study. In-depth semistructured interviews were conducted with 13 participants with chronic conditions who experienced cybervictimization. A codebook was developed, and a zigzag approach to thematic analysis was used to define and refine themes. Ethical considerations and risk assessment were ongoing during the research process because of the sensitivity of the topic and cases of harassment. ResultsCybervictimization has direct and indirect impacts on the self-management of chronic conditions. This impact was verified across 6 overarching themes that emerged from this study. First, biomedical events included overall health deterioration because of existing conditions, new diagnoses, and subjective physical complaints. Second, the impact on mental health was perceived through psychological consequences and psychiatric disorders that developed after or during this traumatic experience. Third, the multilevel impact theme focused on disrupting the strategies for coping with health conditions and involved unplanned changes to victims' health management priorities. Fourth, the impact of complexity reflected the perceived uniqueness in each case, intersectionality, struggle to obtain formal support, and subsequent health complications. Fifth, social network involvement comprised the effects of social isolation, victim blaming, and deception. Finally, the disability discrimination theme focused on prejudice, issues on inclusion, and hostility in society, with subsequent effects on well-being. ConclusionsPeople with long-term conditions experienced different forms of cybervictimization, all disruptive with various effects on health. Disability discrimination was a prominent finding to be further investigated. This paper reports the impact as themes to guide further research and practice, with the recognition that long-term conditions and impairments are not a homogeneous group. Despite the devastating consequences, there are positive points that strengthen potential interventions. Awareness-raising campaigns, training of support channels, and multidisciplinary research are recommended to tackle this issue and initiate change.